ASSOCIATION OF SCHISTOSOMIASIS ENDEMICITY WITH SOCIODEMOGRAPHIC FACTORS IN GIKONKO AND KIBINGO HEALTH CENTRES, KIGALI - RWANDA - , WABWIRE Paul Francis; ICYIZANYE Norbert,; TWAHIRWA Gervais, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Schistosomiasis also known as bilharziasis is among the major endemic parasitic communicable disease commonly found in developing countries including Rwanda and world over. The research aimed at determing the correlation between schistosomiasis with socio-demographic factors and water contact behaviors.It was a descriptive, cross-sectional study that adopted mainly quantitative data collection and analysis pproach in purposively selected population of “391” patients attending health  services. Data was collected and analyzed using SPSS. Cross-tabulation and chi-square were used to determine the association between independent and dependent variable. Findings indicated a high prevelance of 32% being highly associated with none use of shoes among females (p-value = 0.029: CI 95), agriculture activities - in swamps (p-value =0.001: CI 95%),Swimming (p-value=0.001: CI = 95) and bathing in water sources (p-value=0.001 : CI = 95. Conclusivelly, this study indicated that demographic, social and water contact behaviors are among the contributing factors to schistosomiasis endemicity in the research areas.In this case management planners need to include all age groups in mass treatment of the disease, have continuous Health education and community mobilization about the endemicity and morbidity of schistosomiasis in the study areas and country at large.